ANALISIS KELAYAKAN PRODUKSI USAHA DENGAN SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE BENEFIT COST RATIO - Agus Suryadi (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2021)
A decision support system to determine the feasibility of subsequent production at a furniture shop that was studied using the SPK Benefit Cost Ratio method, this decision support system was made using web-based programming and the design of this system used the PHP and MySQL programming languages, drawing conclusions in this decision support system using the method BCR (Benefit Cost Ratio). This BCR method can determine the inadequacy of production that will be planned in the future. This decision support system program will provide a simulation of the results of the BCR to be processed, the results of this study indicate that the Benefit Cost Ratio method can be used to determine the next production because it is able to provide the results of determining production which so far have not used the method to continue production in stores based on the production that has been produced. previously sold. Keywords: System, Support, Decision, UML, MySql, PHP, Production